Generating Pareto Optimal Solutions of Multi-Objective LFPP with Interval Coefficients Using e-Constraint Method - Nayak, Suvasis; Ojha, Akshay (Mathematical Modelling and Analysis, 2015)
This paper illustrates a procedure to generate pareto optimal solutions of multi-objective linear fractional programming problem (MOLFPP) with closed interval coefficients of decision variables both in objective and constraint functions. E-constraint method is applied to produce pareto optimal solutions comprising most preferred solution to satisfy all objectives. A numerical example is solved using our proposed method and the result so obtained is compared with that of fuzzy programming which justifies the efficiency and authenticity of the proposed method.